2000
DOI: 10.1007/bf03020951
|View full text |Cite
|
Sign up to set email alerts
|

Smoking does not alter the dose-requirements and the pharmacodynamics of rocuronium

Abstract: Purpose: Controversial data about the effect of smoking on the dose-requirements and the pharamcodynamics of rocuronium have been reported recently. This study was conducted to evaluate the dose-requirements and the pharmacodynamics of rocuronium in smokers using target controlled infusion. Methods:The dose-requirements of rocuronium for 60 min relaxation, using target controlled infusion, given under intravenous anaesthesia with propofol, fentanyl and nitrous oxide was studied in 37 smokers and 37 nonsmokers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
1
8
0
1
Order By: Relevance
“…Rautoma and Svartling 25 reported a significantly increased requirement for rocuronium in smokers, and Reisli et al 24 reported a significantly longer dur 25 in children with a history of exposure to secondhand smoke than in children without such exposure. Pühringer et al, 26 however, did not find any differences between tobacco smokers and nonsmokers in rocuronium's onset time, peak neuromuscular blockade, and duration of action. Our findings indicate that tobacco smoking history is not an independent predictor of the duration of action of rocuronium, suggesting that the reported association between smoking and increased duration of action of rocuronium 24,25 is not causative.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Rautoma and Svartling 25 reported a significantly increased requirement for rocuronium in smokers, and Reisli et al 24 reported a significantly longer dur 25 in children with a history of exposure to secondhand smoke than in children without such exposure. Pühringer et al, 26 however, did not find any differences between tobacco smokers and nonsmokers in rocuronium's onset time, peak neuromuscular blockade, and duration of action. Our findings indicate that tobacco smoking history is not an independent predictor of the duration of action of rocuronium, suggesting that the reported association between smoking and increased duration of action of rocuronium 24,25 is not causative.…”
Section: Discussionmentioning
confidence: 90%
“…[24][25][26] Variables that correlated significantly (P = .15) with the mean dur 25 were included in our multiple regression analysis model, and an association of variables with the dur 25 of the respective NBD was assumed at a significance level of less than .05.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pühringer et al (16) found that smoking does not change the dose requirement or the pharmacodynamics of rocuronium. Salihoğlu et al (17) discovered a decrease of 25% in the neuromuscular effect of rocuronium, starting time and recovery time in smokers compared with non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nicotine may influence the action of NMBAs at the nicotinic acetylcholine receptors of the neuromuscular junction (5). Recent studies report controversial data about the effects of smoking on the dose requirements of nondepolarizing NMBAs in adults (6–8). Some authors have suggested that nonsmokers are more sensitive to vecuronium than smokers (6) and smoking increases the requirement for rocuronium (7), but others have suggested that smoking does not alter rocuronium‐induced neuromuscular block (NMB) (8).…”
Section: Introductionmentioning
confidence: 99%